Microvascular decompression in the surgical management of trigeminal neuralgia - (:unkn) unknown (Springer-Verlag, 1995)
The pathophysiological mechanisms underlying trigeminal neuralgia are not clearly understood and several therapeutic modalities have been advocated. Microvascular decompression (MVD) is a widely used surgical approach for the decompression of the affected root entry zone (REZ) of the fifth cranial nerve. In this paper, we present our experience based on 32 patients with trigeminal neuralgia who were treated with MVD, and discuss the role of this procedure in the surgical management of trigeminal neuralgia. All patients had typical TN pain and had had previous medical management which was unsuccessful. Fourteen patients (44%) had been previously treated with other surgical procedures and had persisting pain at the time of admission. Preoperatively, computerized tomography was obtained in all patients; twelve patients (37.5%) were evaluated with magnetic resonance imaging. These neuroradiological studies revealed an asymmetrical vascular structure at the involved REZ in nine patients (28%). All patients underwent MVD, and a vascular loop causing compression on the REZ of the fifth cranial nerve was demonstrated in each case. No mortality was observed, and the only permanent morbidity was cerebellar infarction in one patient (3%). Symptorns disappeared in all patients in the early postoperative period, and only three recurrences (12%) were observed within the follow-up period (mean: 26 months). © 1995 Walter de Gruyter & Co.
Keywords: Microvascular decompression; trigeminal neuralgia